Competition in the Natural Gas Industry : The Emergence of Spot, Financial, and Pipeline Capacity Markets - Juris, Andrej (World Bank, Washington, DC, 2012)
Countries in Asia, Europe, and North and South America are introducing reforms to boost efficiency and attract new private investment in their natural gas industries. The trend has been to unbundle along vertical and horizontal lines and to open wholesale gas markets to new entrants. These new entrants stimulate competition and the development of new markets--in gas supply, in financial gas contracts, and in pipeline capacity. Such has been the success of these new markets--especially in the United States and the United Kingdom-- that it has prompted a search for other potential markets in the industry. This Note, part of the broad effort to aid reformers by disseminating knowledge from early reforms, describes the underlying structural and trading arrangements in the gas and pipeline markets. Two companion Notes examine these markets in the United Kingdom and the United States.